Profiles of total and sn-2 fatty acid of human mature milk and their correlated factors: A cross-sectional study in China - Ni, Mengmei; Wang, Yingyao; Yang, Zhirui; Xu, Xuebing; Zhang, Hong; Yang, Yuexin; Zhang, Lishi; Chen, Jinyao (Frontiers in Nutrition, 2022)
Fatty acid (FA) in breast milk is beneficial to the growth and neurodevelopment of infants. However, the structure profiles of breast milk FAs and the influencing factors which are crucial for normal function have not been fully elucidated. This study aimed to characterize the profiles of total and sn-2 FAs in human mature milk based on two representative urban areas in China and explore potential sociodemographic determinants. Mothers (n = 70) at 40–100 d postpartum from Beijing and Danyang were recruited according to unified inclusion and exclusion criteria. Total and sn-2 FA compositions were examined by gas chromatography and quantified. Using the Spearman correlation and multiple regression model, we found that the location and maternal education level were the most conspicuous correlated factor. The milk of mothers from Beijing had higher levels of the n-6 series of long-chain polyunsaturated fatty acids (LCPUFA) (C20:2, C20:3n-6, C20:4n-6, n-6PUFA/n-3PUFA, LA/ALA, and ARA/DHA) than that of Danyang, while the opposite was observed in the n-3 series of LCPUFA (C18:3n-3 and Total n-3PUFA). Compared to the milk of mothers with a high school degree or below, those with a bachelor's degree or above had lower SFAs (C10:0, C12:0, C14:0, and Total SFA), n-3 series of LCPUFA (C18:3n-3 and Total n-3PUFA), C18:1n-9t, and higher n-6 series of LCPUFA (C18:2n-6c, C20:2, C20:4n-6, Total n-6PUFA, and n-6PUFA/n-3PUFA). Maternal age, infant gender, pre-conception body mass index (BMI), parity, delivery mode, and gestational weight gain were also associated with total FAs. However, fewer associations were found between the above factors and sn-2 FAs. This study will promote an understanding of human breast milk's lipid profile and help develop a formula more suitable for infants.